Studies on the Use of Unconventional Transport Vehicles and Fuels in the Island of Crete, Greece - Vourdoubas, John (Environmental Management and Sustainable Development, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Several alternative vehicles and zero-carbon fuels have been developed and used to mitigate climate change, reduce the air pollution in cities and the dependence on oil resources. Their use is necessary for achieving the net-zero emissions target in the next decades. Among these vehicles are electric vehicles and vehicles with ICEs using electricity, hydrogen and bio-fuels of organic origin. The possibility of using alternative vehicles and fuels in Crete, Greece for de-carbonization of vehicles transportation has been examined. The use of electric vehicles equipped with re-chargeable electric batteries, electric vehicles equipped with fuel cells using hydrogen and vehicles with internal combustion engines using bio-fuels has been studied. The required electricity for re-charging electric batteries and for electrolytic hydrogen production can be generated from the abundant local solar and wind energy resources. Taking into account the maturity and the cost-effectiveness of the solar-PV technology as well as the wind turbine’s technology in Crete the use of electric vehicles powered by green electricity is prioritized for the green transition of the transportation sector. Bio-fuels which are used in conventional vehicles are not produced in the island. Each type of the abovementioned vehicles and fuels has several advantages and drawbacks which can accelerate or delay their use in Crete. It has been found that the green transition of vehicles transportation in the island has positive and negative economic impacts to all stakeholders. The results could be useful to policy makers, local authorities and to local stakeholders while they can assist in the development of a plan for de-carbonizing the island by 2050.